Algebra and Trigonometry 10th Edition

Published by Cengage Learning
ISBN 10: 9781337271172
ISBN 13: 978-1-33727-117-2

Chapter 3 - 3.2 - Polynomial Functions of Higher Degree - 3.2 Exercises - Page 261: 62



Work Step by Step

$f(x)=a(x-3)[x-(2+\sqrt 7)][x-(2-\sqrt 7)]=a(x-3)[(x-2)-\sqrt 7][(x-2)+\sqrt 7]=a(x-3)[(x-2)^2-(\sqrt 7)^2]=a(x-3)(x^2-4x+4-7)=a(x-3)(x^2-4x-3)=a(x^3-7x^2+9x+9)$ $a$ can be any value. If $a=1$: $f(x)=x^3-7x^2+9x+9$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.